Analysis of the Impact of the Public Boycott Trend on the Financial Statements of PT Unilever Indonesia Tbk Using the Ratio Analysis Method - Aurelia Shafarina Firdausi (Journal of Economic and Business Analysis, 2024)
The conflict between Israel and Palestine that occurred again in the Gaza Strip in October 2023 had a significant impact not only on the two countries but also on almost all countries in the world, including Indonesia. The boycott action carried out by the community against several companies that provide support in the genocide committed by the Israeli side is enough to have an impact on the financial stability of several companies. One of the companies that is also the target of this boycott is PT Unilever Indonesia Tbk. The method used in this study is to use some financial ratio analysis on the annual financial statements of PT Unilever Indonesia Tbk in 2022, namely before the boycott and in 2023, namely when the boycott occurred. The results of the financial ratio analysis show that the boycott has a significant impact on the company's financial stability, liquidity, solvency, and profitability.